Biomechanical and Structural Parameters of Tendons in Rats Subjected to Swimming Exercise - Bezerra, M. A.; Santos de Lira, K. D.; Coutinho, M. P. G.; de Mesquita, G. N.; Novaes, K. A.; da Silva, R. T. B.; de Brito Nascimento, A. K.; Inácio Teixeira, M. F. H. B.; Moraes, S. R. A. (International Journal of Sports Medicine, 2013)
The aim of this study was to evaluate the effect of swimming exercise, without overloading, on the biomechanical parameters of the calcaneal tendon of rats. 27 male Wistar rats (70 days) were distributed randomly into 2 groups, Control Group (CG; n=15) with restricted movements inside the cage and Swimming Group (SG; n=12), subjected to exercise training in a tank with a water temperature of 30±1°C, for 1 h/day, 5 days/week for 8 weeks. All animals were kept in a reversed light/dark cycle of 12 h with access to food and water ad libitum. After that, they were anesthetized and had their calcaneus tendons collected from their left rear paws. The tendon was submitted to a mechanical test on a conventional test machine. From the stress vs. strain curve, the biomechanical data were analyzed. For the statistical analysis, the Student-T test was used (p<0.05). Of the variables examined, the maximum tension (p=0.009), maximum force (p=0.03), energy of deformation/tendon cross sectional area (p=0.017) and elastic modulus of the tendon (p=0.013) showed positive outcomes in SG. There was no difference in the other parameters. The results indicate that the swimming exercise training, without overloading, was an important stimulus for improving the biomechanical parameters and structural properties of the calcaneal tendon.
Keywords: exercise; biomechanics; animal model; connective tissue